(3eNJUQ GdecGJHGJ GdHOjYI ajeG jcJH ef CehQ GdTQjYIs - (3eMeO Hf YHO GdQMef Hf YHO GdYRjR GdeNOhej GdNGdOjs
(3ChdgG (B:s
(3hHYO adeG cGfJ GdcJGHI efOhHG EdjgG eMQVG ef GdTGQY YdjgG s
(3BNQgG (B:s
(3GdCOYjI HOhGe GjGe gPg GdOhdI GdRGgOI hNdhO ddSYGOg Ydi ehdGfG GdebQ GdeNOhei s
(3HgG fXGe GdJYbjHIs
(3hgh eNJUQ LGeYI GdYbhO ai Yde GdehGKjb hGdYghOs
(3jdjg HYV ahGFO ai GdehVhY faSg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNGdOjI HGdbOS (B(247) s
Keywords: (3Gdabg GdMfHdjs